A study on the customer satisfaction on products traded in Sawit Kinabalu Edible Oils / Wilbur Mark Suinggi - Mark Suinggi, Wilbur (2008)
Customer dissatisfaction may arise when products they buy is not up to their expectations due to some inefficiency of the Service of an organization. The study aimed to measure the level of customer satisfaction of products traded in Sawit Kinabalu Edible Oils. Products and Service delivered to the buyers is satisfied by the customers and the organization is well managed. Key findings were that certain area in the service at the refinery was not efficiently designed. Responses from the customers tell that even though the staffs produced quality product, but still quite a number of customers were unhappy on certain matter especially on the quantity variance and loading time. This paper concludes with suggestions for future research and managerial implications.